Blog: uma proposta para a prática de multiletramentos na escola - Castro , Maria Morganna da Silva (2014)
The practice of reading and writing in school settings has had to live with a conflict: our students are surrounded by media far more attractive than paper and pencil and these are seen as rivals of teaching and learning, but the truth is that in many of these our students read what is published and they write, comment, give their opinions, however cannot stand linear reading and writing imposed on paper. Given that we can no longer ignore this reality, we look at the use of the forms of reading and writing that new technologies can provide. Thus, this research is guided by the following questions: how to combine the use of new technologies to the teaching and learning of reading and writing process? How can we explore the multi-literacies in reading and writing activities in the classroom? Considering the hypothesis that the use of the blog contributes to the practice of multiliteracies in school, our general objective is to develop a didactic proposal that contributes to the practice of multi-literacies, using the blog as a tool for streamlining the activities developed in the network with the purpose of analysis and production of gender virtual propaganda. Therefore, we developed a qualitative study in which we fulfil steps like the literature review of the relevant theory, exploratory research instruments and application of a proposed instructional sequence in class 9 of the Basic Education School at Suzete Dias Correia, where we teach Portuguese. The intervention in our practice configures an action research, which in turn enables the collection of data for subsequent reporting and the experience and assessment of the results with the proof of our hypothesis. The results find that the blog contributes to the development of multi-literacy skills , in that students read and interpret the blog‟s interface , posted and produced beyond these discursive genres , interact with multimodal texts , learn to relate senses , research and select information to exchange knowledge , among other skills . For the development of research, we used the theoretical studies of Bakhtin (2000 ), Marcuschi ( 2001, 2002 ), Xavier (2005 ) , Rojo (2012 ), among others, that underlie about discursive genres, blog , multi-literacy and multimodality .